2019
DOI: 10.1186/s12913-019-4223-x
|View full text |Cite
|
Sign up to set email alerts
|

International survey of De-implementation of initiating parenteral nutrition early in Paediatric intensive care units

Abstract: Background: Initiating parenteral nutrition (PN) within 24 h in critically ill children is inferior to withholding PN during the first week, as was found in the PEPaNIC study. The aims of this study were to investigate deimplementation of early initiation of PN at PICUs worldwide, and to identify factors influencing de-implementation. Methods: A cross-sectional online survey was conducted (May-October 2017), consisting of 41 questions addressing current PN practices, the degree of de-implementation, and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…A summary of comparisons between our recommendations and those presented by ASPEN/SCCM is shown in Table 2. Table 2) which helps assist in the uptake and implementation of guidelines into practice [21]. Implementation of evidence into clinical practice remains problematic, in 2017 a European survey of 59 PICUs found that 69% of PICUs still had no local feeding guidelines [13].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of comparisons between our recommendations and those presented by ASPEN/SCCM is shown in Table 2. Table 2) which helps assist in the uptake and implementation of guidelines into practice [21]. Implementation of evidence into clinical practice remains problematic, in 2017 a European survey of 59 PICUs found that 69% of PICUs still had no local feeding guidelines [13].…”
Section: Resultsmentioning
confidence: 99%
“…Our finding of evidence of greater morbidity in survivors who received early PN is in keeping with evidence in critically ill adults, children and term neonates, which has led to calls for the de-implementation of early PN in these groups. 21 The mechanisms that explain the adverse outcomes in paediatric patients are equally likely to play a role in preterm infants. A secondary analysis of the PEPaNIC trial (The Early versus Late Parenteral Nutrition in the Pediatric Intensive Care Unit), comparing early versus delayed PN in critically ill children and babies, found that it was the early administration of amino acids, but not glucose or lipids, that explained the harm from early PN.…”
Section: Discussionmentioning
confidence: 99%
“…The late PN group had lower odds of infection, shorter duration of mechanical ventilation, shorter duration of PICU and hospital stay (17) . When another worldwide survey was conducted by van Puffelen et al (18) , 1 year after the publication of the PEPaNIC trial (17) , only five units (12 %) reported changing their practice from early to late commencement of PN (18) . Although the short timeframe between the publication of the RCT and the survey may be the main reason for the low rate of change in clinical practice, concerns about the risk of hypoglycaemia and the perceived limited external validity of the PEPaNIC trial may also have prevented clinicians from changing their clinical practice (19)(20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%